Digitizing Tolerance Practices as an Effort to Prevent Religious Conflict in Aceh through New Media - Fathayatul Husna; Annisa Zulkarnain (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
This article opens an academic discourse on tolerance campaign strategies as a new form of conflict resolution in Aceh. LABPSA is an institution that accommodates young people to campaign for tolerance, inclusiveness, gender equality, and other social issues. All participants who join LABPSA carry out various tolerance campaign strategies. These strategies focus on how young people optimize social media to campaign for issues of tolerance. The data collection process is carried out by studies based on virtual ethnographic methods and online documentation. This step was carried out by looking at the landscape of religious conflicts that occurred in Indonesia, especially in Aceh province. What is the role of the Aceh government in carrying out conflict resolution to resolve religious conflicts in Aceh? What form of active participation did young people take when voicing the issue of tolerance through LABPSA? The results of this study are that the presence of young people under the LABPSA institution is a new way to voice acts of tolerance and resolve religious conflicts in Aceh. The various activities carried out are a form of dissatisfaction with the Aceh government's response to the issue of intolerance. On the other hand, the presence of young people in LABPSA is also part of helping the Aceh government resolve conflicts in Aceh, especially religious conflicts, and eradicating issues of intolerance.